Applicability of mode II interlaminar fracture toughness testing methods for characterization of thermoplastic laminates with woven fabric reinforcements. (July 2019) - Wilk, Jakub
Highlights: Comparison of ASTM D7905 and ISO 15114 for mode II interlaminar fracture toughness. Fracture toughness of PEEK reinforced with woven fabric carbon fiber. Consistent results with low coefficient of variation obtained for 5HS CF/PEEK. Modification of the procedures accommodating thermoplastic laminates with fabric reinforcement. Abstract: The scope of both existing standardized methods for the determination of quasistatic mode II interlaminar fracture toughness, ASTM D7905 /D7905M – 14 and ISO 15114:2014, is limited to testing laminates with unidirectional reinforcement. Furthermore the precision round-robins conducted as a part of the development of these procedures focused mainly on laminated with epoxy resin matrix. This paper compares the testing methods for quasistatic mode II interlaminar fracture toughness with the focus on their applicability to testing thermoplastic laminates with woven fabric reinforcement. Two standardized testing methods were used to determine the mode II fracture toughness of a laminate made of polyether ether ketone matrix reinforced with T300 carbon fibers in the form of 5 harness satin woven fabric. The testing methods were compared in terms of the set-up complexity, testing efficiency, the data reduction methods, the type of properties determined, the results scatter and the applicability to testing thermoplastic-based laminates with woven fabric reinforcement. The methods produced similar and consistent results. Both of them can be successfully applied to testing thermoplastic laminates with woven fabric reinforcement after including modifications discussed in the paper.